Rosuvastatin Treatment Reduces Markers of Monocyte Activation in HIV-Infected Subjects on Antiretroviral Therapy - Funderburg, Nicholas T.; Jiang, Ying; Debanne, Sara M.; Storer, Norma; Labbato, Danielle; Clagett, Brian; Robinson, Janet; Lederman, Michael M.; McComsey, Grace A. (Clinical infectious diseases, 2014)
Background. Statins, or 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, have anti-inflammatory effects that are independent of their lipid-lowering properties. Despite suppressive antiretroviral therapy (ART), elevated levels of immune activation and inflammation often persist. Methods. The Stopping Atherosclerosis and Treating Unhealthy Bone With Rosuvastatin in HIV (SATURN-HIV) trial is a randomized, double-blind, placebo-controlled study, designed to investigate the effects of rosuvastatin (10 mg/daily) on markers of cardiovascular disease risk in ART-treated human immunodeficiency virus (HIV)–infected subjects. A preplanned analysis was to assess changes in markers of immune activation at week 24. Subjects with low-density lipoprotein cholesterol <130 mg/dL and heightened immune activation (%CD8 + CD38 + HLA-DR + ≥19%, or plasma high-sensitivity C-reactive protein ≥2 mg/L) were randomized to receive rosuvastatin or placebo. We measured plasma (soluble CD14 and CD163) and cellular markers of monocyte activation (proportions of monocyte subsets and tissue factor expression) and T-cell activation (expression of CD38, HLA-DR, and PD1). Results. After 24 weeks of rosuvastatin, we found significant decreases in plasma levels of soluble CD14 (-13.4% vs 1.2%, P = .002) and in proportions of tissue factor–positive patrolling (CD14 Dim CD16 + ) monocytes (-38.8% vs -11.9%, P = .04) in rosuvastatin-treated vs placebo-treated subjects. These findings were independent of the lipid-lowering effect and the use of protease inhibitors. Rosuvastatin did not lead to any changes in levels of T-cell activation. Conclusions. Rosuvastatin treatment effectively lowered markers of monocyte activation in HIV-infected subjects on antiretroviral therapy. Clinical Trials Registration. NCT01218802.